Association of GGH Promoter Methylation Levels with Methotrexate Concentrations in Chinese Children with Acute Lymphoblastic Leukemia. Issue 7 (16th June 2020) - Wang, Shu‐Mei; Kong, Xiao‐Yan; Li, Miao; Sun, Lu‐Lu; Yan, Dan
Abstract : Background: It is known that γ‐glutamyl hydrolase (GGH) is involved in the disposition of methotrexate (MTX), and GGH activity is regulated by DNA methylation in acute lymphoblastic leukemia (ALL) cells. The present study explores the methylation status of the GGH promoter in peripheral blood and its association with MTX levels and toxicities in Chinese children with ALL. Methods: Serum MTX concentrations were determined by fluorescence polarization immunoassay. Methylation quantification and genotyping for GGH rs3758149 and rs11545078 was performed by Sequenom MassARRAY in 50 pediatric patients with ALL. Results: Overall, the investigated region of the GGH promoter was in hypomethylated status. The methylation levels of cytosine phosphate guanine (CpG)_7, CpG_12, CpG_17, and CpG_20 were significantly higher in patients with B‐cell ALL than other immunotypes (p<0.05). The methylation levels of CpG_13.14, CpG_17, and CpG_19 showed a significant negative correlation with MTX C24 hr (p<0.05). The methylation level of CpG_8.9 correlated significantly with MTX C42 hrs (p<0.05). The methylation level of CpG_19 was significantly lower in patients with MTX toxicities (p<0.05). Conclusions: The methylation levels of the GGH promoter might affect MTX exposure and toxicities. These findings provided reasonable explanations for the variability of MTX responses in patients with childhood ALL.